Survival of children with acute leukaemia in paediatric oncology HUSM from 1990 to 2010 - Zahari, Nor Fadhilah (2013)
Introduction It is well known that there is difference in survival of children with acute leukaemia between developed and developing countries. However, there are lack of reports in the treatment outcome and the survival of children with acute leukaemia in developing countries including Malaysia. To date, there is no published study predicting the treatment outcome in Hospital USM. Objectives The objectives of this study were to evaluate the overall survival (OS) and event free survival (EFS) rate and to identify factors that determine the EFS of childhood Acute Lymphoblastic Leukaemia (ALL) and Acute Myeloid Leukaemia (AML) in Hospital USM. Methodology This study was a retrospective record review of children from newborn to 12 years old who were diagnosed with ALL and AML and received chemotherapy in Paediatric Oncology Unit Hospital USM from year 1990 to 2010. Children who were recruited were identified from registry in paediatric oncology unit and medical records in Hospital USM. Multiple Cox Regression model was used to predict the poor prognostic factors for increased risk of death or relapsed for ALL and AML separately.Results There were 334 acute leukaemia children (257 ALL and 77 AML) in the registry. Out of these, 224 ALL and 59 AML were enrolled, giving a response rate of 87% for ALL and 77% for AML. The mean duration of follow up was 73 months. The OS rate for ALL at 1, 3 and 5 years were 77.7%, 66.9% and 63.5% respectively and for AML were 59.3%, 41.4% and 39.1% respectively. The EFS rate for ALL at 1, 3 and 5 years were 69.6%, 54.1% and 47.8%, for AML were 52.0%, 40.6% and 38.1% respectively. Multivariate analysis showed that the independent poor prognostic factor for ALL are presenting age at diagnosis; age above 10 years old (HR 3.6; 95% CI: 1.9-6.7), and aged between 5 to 9.9 years old (HR 1.6; 95% CI: 1.1-2.4). Similar analysis showed that spleen size > Scm (HR 4.1; 95% CI: 1.4-11.1 ), and treatment protocol with AML BFM-87 (HR 2.9; 95% CI: 1.3-6.3) were independent poor prognostic factors for AML compared to spleen size~ Scm and AML 12 UK protocol. Conclusion Survival rate in this study was comparable to developing countries but remained low compared to developed countries. The study had also identified a few prognostic factors for increased risk of death and relapsed in ALL and AML for the local set up.